Editorial: Journal of Pragmatic Constructivism creates understanding about functioning practices - Jakobsen, Morten; Korhonen, Tuomas; Laine, Teemu (Journal of Pragmatic Constructivism, 2021)
This editorial introduces the journal and the content of the issue